1987
DOI: 10.1111/j.1365-2621.1987.tb06704.x
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Interpretation of Textural Changes in Black Beans During Prolonged Storage

Abstract: Control and roasted (SO"C), dry black beans (Phasedus vulgaris) were stored for 9 months at 8, 10, 12, and/or 14% moisture content and 8.5", 25", and 40°C. Similarly, beans heated in a solid-to-solid roaster to 51", 61", 72.3", 80", 85.5", 89.5', lOI", and 111°C were maintained at 8% moisture and 25°C. Final hardness increased with moisture content and temperature. Hardening at 8.5" and 25°C proceeded initially almost linearly reaching a constant value after 4 to 6 months while at 40°C it was sigma-shaped. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…A study on black bean storage revealed an increase in cooked bean hardness with an increase in storage period (9 months), moisture content (8%, 10%, 12%, and 14%), and storage temperature (8.5, 25, and 40 °C) as compared to untreated beans at 10.5% moisture (Aguilera & Ballivian, ). Significant differences in hardness values were reported with moisture and temperature increases.…”
Section: Grain Legumes Entering the Millmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on black bean storage revealed an increase in cooked bean hardness with an increase in storage period (9 months), moisture content (8%, 10%, 12%, and 14%), and storage temperature (8.5, 25, and 40 °C) as compared to untreated beans at 10.5% moisture (Aguilera & Ballivian, ). Significant differences in hardness values were reported with moisture and temperature increases.…”
Section: Grain Legumes Entering the Millmentioning
confidence: 99%
“…The classic manifestation of this for grain legumes is the development of the hard-to-cook phenomenon in stored beans. Depending on a number of factors (Reyes-Moreno & Paredes-Lopez, 1993), especially storage conditions (Aguilera & Ballivian, 1987;Coelho, de Mattos Bellato, Santos, Ortega, & Tsai, 2007), components (starch, protein, and fiber) within the grain legume undergo molecular rearrangement, impairing bean quality as a result of developing unacceptable hardening that cannot be softened by cooking (Reyes-Moreno, & Paredes-Lopez, 1993).…”
Section: Factors Affecting Grain Legume Millabilitymentioning
confidence: 99%
“…EXTENDED STORAGE at high temperature and high humidity has been associated with development of the hard-to-cook defect in a limited number of legume varieties (Aguilera and Ballivian, 1987;Burr et al, 1968;Jackson and Varriano-Marston, 1981;Jones and Boulter, 1983;Kon, 1968;Kon and Sanshuck, 1981). Burr et al (1968) found that lima beans and Sanilac beans at 14% moisture stored at 32°C for one year had g-fold and 17-fold increased cooking times, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…Hardness and moisture content of beans as well as the temperature and relative humidity of the chambers were determined regularly. Bean soaking and cooking was as described in Aguilera and Ballivian (1987). Hardness of beans was expressed relative to the initial hardness at storage time 0 or F/F,.…”
Section: Storage In Simulated Tropical Conditionsmentioning
confidence: 99%
“…Beans kept at 35% W and 15°C for approximately one year showed no significant hardening although many indicators of biochemical changes such as the amount of extractable phenols and in virro peroxidase activity varied during storage (Plhak et al 1987). The strong dependence of hardness on moisture content (or water activity) has been interpreted as a diffusional control of the hardening process (Aguilera and Ballivian 1987). Nevertheless, achieving low moisture content may be expensive, difficult to attain technically and result in seed coat cracking.…”
Section: Introductionmentioning
confidence: 99%